PERSEPSI REMAJA TERHADAP SEXTING DI MEDIA SOSIAL - Rafles Abdi Kusuma (MEDIOVA: Journal of Islamic Media Studies, 2021)
This article aims to discuss about sexting, which is a social phenomenon that is currently happening, especially among teenagers. Sexting activity is a method of interaction through social networks in adolescents that is being reconstructed and redefined through communication technology. The vulnerability of teenagers to sexting on social media cannot be denied. A sexting case recently occurred in Bangka 2019, namely a threat to young women from Pangkalpinang who were forced to do topless chests while making video calls on whatsapp social media. Based on a review of previous studies examining the phenomenon of sexting, the findings of these studies have shown a tendency for teenagers in the world to consider sexting a "normal" activity. Therefore, it is necessary to understand how teenagers perceptions on sexting. So that various educational efforts to overcome the negative impact of internet use related to pornography in Indonesia can be maximally and accurately targeted.